Analysis of E-Government Health Application Features Acceptance on Partner Applications During COVID-19 - Nuraini, Wan Azizah Sri; Mardhiana, Hawwin; Kusumawati, Aris (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
This study analyzes the factors that influence public acceptance of E-Government Health Application feature on partner applications. The current phenomenon in the health sector is the emergence of COVID-19 which has a very fast rate of human-to-human spread. To handle these cases, the government evaluates and looks for new innovations by cooperating with new partners and making E-Government Health Application feature accessible through partner applications to make it easier for the public. The successful use of the system is influenced by the acceptance and use of the individual who uses it. The research model used in this study is a modified UTAUT2 model with a total sample of 250 respondents. Model testing is done by statistical analysis using SmartPLS software. It was found that Facilitating Conditions and Behavioral Intention variables had a positive and significant effect on Use Behavior variable with t-statistic of 3.659 and 4.505. Habit had a positive and significant effect on Behavioral Intention and Use Behavior variables with t-statistic of 7.939 and 3.232. Meanwhile, the Experience moderating variable affects the Facilitating Condition on Behavioral Intention variable and affects the Behavioral Intention on Use Behavior variable with t-statistics of 2.069 and 1.972